Heterotopic Pancreatic Neoplasm Presenting as an Obstructing Mass at the Fourth Portion of the Duodenum - Stock, Cameron; Keutgen, Xavier M; Pisapia, David; Crawford, Carl; Zarnegar, Rasa (JOP. Journal of the Pancreas, 2011)
Context Heterotopic pancreatic adenocarcinoma is a rare finding at laparotomy. Herein we present the case of a patient with malignant transformation of a heterotopic pancreas located in the fourth portion of the duodenum. Case report A 79-year-old woman was admitted to the surgery service with complaints of early satiety and abdominal fullness progressively worsening over the previous two years. A computed tomography scan of the abdomen and an upper endoscopy revealed an obstructing mass in the fourth portion of the duodenum, biopsies were negative for carcinoma. A segmentectomy of the third and fourth portions of the duodenum was performed. Post-operative histology revealed malignant transformation of a heterotopic pancreas. The patient had an unremarkable postoperative recovery and was discharged home. Conclusion In evaluation of patients with distal duodenal masses, we report that heterotopic pancreatic neoplasms should be considered in the differential diagnosis. Image: Image of the mass from upper endoscopy.